The Relationship Between Bilingual Language Control and Language Dominance: An Empirical Study of Visual Language Perception. - Revniuk, Volodymyr; Bátyi, Szilvia (East European Journal of Psycholinguistics, 2023)
Bilingual visual perception is an under-researched area in psycholinguistics and has yielded contradictory results regarding language control. Two theories were developed to account for visual language perception in bilinguals - the Inhibitory Control model (Green, 1986) and the Bilingual Interactive Activation model (Grainger and Dijkstra, 1992). Even though these two accounts have opposite predictions for asymmetrical language control (different for the bilingual's L1 and L2), most research up to date found evidence only for symmetrical control (Macizo et al., 2012; Orfanidou and Summer, 2005). This study aims to investigate the influence of language dominance on the visual language perception of bilinguals and providing evidence for the accountability of the models mentioned above. Thirty-one Hungarian-English bilinguals were recruited for this study. Participants' language dominance was operationalized by a complex score using the Bilingual Language Profile questionnaire (Birdsong et al., 2012). The bilingual lexical decision task was used to investigate the differences in the cognitive processing of the two languages. Target stimuli were carefully matched for their visual and linguistic features to eliminate the potential confounding influences on their perception during task performance. For unbalanced, L1 dominant bilinguals, asymmetrical, dominance-related switching cost was observed, indicating the relevance of the Inhibitory Control model. Faster L2 processing correlated with a richer history of L2-associated experiences and more balanced bilingualism. However, no correlations were found with the frequency of language use, language attitudes, and only weak correlations were observed with language proficiency. The current research proposes a methodological framework for measuring the influence of linguistic background on language switching cost that could ensure comparability between further studies.